The Effect of Using the Project Based Learning (PjBL) Learning Model to Increase UPI YPTK Padang Students' Understanding of the Application of Basic Physics Courses - Zakirman Zakirman (JURNAL PENDIDIKAN MIPA, 2023)
The linkage and coherence of Basic Physics material with material applications in real life is a new problem in Basic Physics lectures at Putra Indonesia University YPTK Padang. The purpose of this study was to see the effect of using the PjBL model to increase students' understanding of the application of the Basic Physics course. This type of research was a quasi-experimental involving a research sample of Informatics Engineering students at the Faculty of Computer Science UPI YPTK Padang who took the Basic Physics course in the 2019/2020 academic year. The sampling technique used is random sampling. In this study the sample class was divided into two categories, namely the experimental class of 51 students and the control class of 51 students. The instrument used is a work assessment sheet in the form of a portfolio. The data analysis technique used was an independent sample t-test, with prerequisite tests first being carried out, namely normality and homogeneity tests. Based on the results of the data analysis performed, the sig-2 tailed value for the independent sample t-test was 0.00 < of the value α = 0.05 . The conclusion from this study is that there are differences in student understanding between classes whose lectures use the PjBL model and classes that carry out conventional learning.